2020
DOI: 10.3390/insects11120870
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Attract-and-Kill Device for the Asian Citrus Psyllid Diaphorina citri (Hemiptera: Liviidae)

Abstract: Phytophagous insects, including Asian citrus psyllids (Diaphorina citri Kuwayama), use multiple sensory modalities (vision, olfaction, and gustation,) to locate and accept host plants. We explored incorporation of several sensory cues into a multi-modal attract-and-kill device (AK device) using a three-dimensional shape to increase visibility, as well as elements of color, attractant, phagostimulant, UV reflectant, and toxicant. Attraction of adult D. citri to the device was mediated by a combination of a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Compared with either olfactory or visual stimuli alone, combining the visual and olfactory cues may augment the accuracy of discriminating between hosts from nonhosts, mates from nonmates and specific parts of host plants, for example. These synergistic responses of insects to host plants and mates using visual, olfactory and tactile cues have been reported previously 36–39 . In our study, we combined the best visual cue and pheromone blends to increase the attraction and capture of L. lineolaris .…”
Section: Discussionsupporting
confidence: 73%
“…Compared with either olfactory or visual stimuli alone, combining the visual and olfactory cues may augment the accuracy of discriminating between hosts from nonhosts, mates from nonmates and specific parts of host plants, for example. These synergistic responses of insects to host plants and mates using visual, olfactory and tactile cues have been reported previously 36–39 . In our study, we combined the best visual cue and pheromone blends to increase the attraction and capture of L. lineolaris .…”
Section: Discussionsupporting
confidence: 73%
“…The olfactometer experiments revealed no significant attraction of C. pyri females to pear odors, indicating that host selection of C. pyri may not be based on plant volatiles alone. Previous studies on other psyllid species highlighted the importance of visual cues on host selection (Farnier et al 2018 ; George et al 2020 ; Patt et al 2011 ; Wenninger et al 2009 ). Further research should be undertaken to investigate the role of visual cues and possible synergistic effects of olfactory and visual cues for host detection of C. pyri .…”
Section: Discussionmentioning
confidence: 99%
“…For example, traps baited with a putative sex pheromone captured more psyllids than no baited ones (Zanardi et al 2018). Recently, it has been reported that cylindrical yellow traps impregnated with an attractive lure and a pyrethroid were more effective in attracting and killing psyllids than standard yellow sticky traps (George et al 2020a).…”
Section: Figurementioning
confidence: 99%